Selection of the industrialized building material supplier by analytic hierarchy process method - Moravveji, Mohammad Yousef (2013)
Industrialized Building system (IBS) aims to expedite the process of installation and construction at site. Industrialized Building System (IBS) is a construction system that is built using pre-fabricated components. The manufacturing of the components is systematically done using machine, formworks, and other forms of mechanical equipment. The components are manufactured off-site and once completed will be delivered to construction sites for assembly and erection so that it could be a area of concern to select the appropriate material from qualified supplier with consideration of critical factor. This project focuses on the issue of industrialized building material while it takes account of minimizing the cost and time of the purchasing and erection process. As the supplier selection is the multi criteria problem the research writer tend to use the Analytic Hierarchy Process which is the most popular decision making method to deal with the issue of IBS-M supplier selection. The imperative criteria for supplier selection problem have been identified to comply with the characteristics of Industrialized Building Material (IBM) Suppliers. A systematic approach has been developed by using Analytic Hierarchy Process method to facilitate the supplier selection taking into account of all identified criteria. Supplier Selection Model (SSM) is proposed to choose the best Industrialized Building Material (IBM) Suppliers for Industrialized Building System IBS companies. The practicability of the developed model has been proved through case study.